2014
DOI: 10.1002/anie.201400750
|View full text |Cite
|
Sign up to set email alerts
|

Transition‐Metal‐Free BF3‐Mediated Oxidative and Non‐Oxidative Cross‐Coupling of Pyridines

Abstract: We report a BF3-mediated direct alkynylation of pyridines at C(2) by using a variety of alkynyllithium reagents (oxidative cross-coupling). Moreover, we have developed a novel transition-metal-free cross-coupling method between alkylmagnesium reagents and 4-substituted pyridines, such as isonicotinonitrile and 4-chloropyridine, by employing BF3⋅OEt2 as a promoter. The combination of these methods enabled us to efficiently prepare a range of di-, tri-, and tetrasubstituted pyridines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 40 publications
0
28
0
1
Order By: Relevance
“…Next, substituent effects of the pyridine ring were studied because electron-donating groups increase the basicity of the ring nitrogen and electron-withdrawing groups diminish the electron density of the ethynyl group. 11 In the case of 3Ka , the reaction was suppressed, and severe conditions were required because stabilization of the pyridinium cation by the electron-donating group, especially in the case of 3Ka , could not diminish the electron density of the ethynyl group sufficiently (entries 10 and 11, Scheme 3). On the other hand, electron-withdrawing groups promoted the reactivity for hydrochlorination to afford the corresponding products 5Ma and 5Na in moderate yields (entries 12 and 13).…”
Section: Resultsmentioning
confidence: 99%
“…Next, substituent effects of the pyridine ring were studied because electron-donating groups increase the basicity of the ring nitrogen and electron-withdrawing groups diminish the electron density of the ethynyl group. 11 In the case of 3Ka , the reaction was suppressed, and severe conditions were required because stabilization of the pyridinium cation by the electron-donating group, especially in the case of 3Ka , could not diminish the electron density of the ethynyl group sufficiently (entries 10 and 11, Scheme 3). On the other hand, electron-withdrawing groups promoted the reactivity for hydrochlorination to afford the corresponding products 5Ma and 5Na in moderate yields (entries 12 and 13).…”
Section: Resultsmentioning
confidence: 99%
“…Tr aditional Chichibabin reactions involve the addition of nucleophiles to activated pyridines,a lthough they generally show poor regioselectivity (Scheme 1a). [2][3][4] Enhanced regioselectivity has been observed by Knochel and co-workers by using substrates with electron-withdrawing groups at C3. [5] Alternatively,M inisci reactions feature addition of alkyl or aryl radicals to aheteroarene.P oor regioselectivity is usually observed, and the 2-substituted products generally predominate (Scheme 1b).…”
mentioning
confidence: 84%
“…[5] Additionally,a lkyl, aryl, and vinyl Grignard reagents provided the pyridines in high yields.T wo cyclopropyl Grignard reagents were incorporated without any evidence of ring opening (41, 42). Overall, the reaction is notable for its ability to 1) incorporate sp 3 -, sp 2 -, and sp-hybridized carbon nucleophiles,2 )accommodate organolithium, organozinc, and organomagnesium reagents,a nd 3) introduce electrophilic functional groups including nitriles and esters.…”
mentioning
confidence: 99%
“…In 2013 and 2014 Knochel and co-workers reported nucleophilic additions to pyridines mediated by BF 3 . 31,32 They found that the formation of pyridine-BF 3 adducts has a dramatic effect on the reaction course. Indeed, some reactions do not occur without the presence of BF 3 and, in other instances, the regioselectivity towards the product of addition to the 4-position is attributed to BF 3 complexation.…”
Section: Scheme 1 Proposed Mechanism Of the Chichibabin Reactionmentioning
confidence: 99%